Clinical achievement improvement through experiential learning-based training - Fitri Chandra Kuspita; Tintin Sukartini; Ahsan Ahsan; Nursalam Nursalam; Apriyani Puji Hastuti (PAGEPress Publications, 2024)
This study aimed to enhance clinical educators' competence through experiential learning-based preceptorship training. Many clinical educators struggle with implementing effective clinical education, providing guidance, and having limited time for new nurses. The research employed a quasi-experimental design with a pre-posttest control group involving 60 clinical educators. The intervention group received a five-day training module using experiential learning-based preceptorship, while the control group received standard intervention. Data analysis used the Wilcoxon Signed Rank Test to analyse differences before and after intervention, and used Mann-Whitney to analyse differences between the two groups. Analysis revealed significant improvements in critical thinking, patient safety, leadership, communication, research-based practice, and professional development among the intervention group compared to the control group (p-value=0.000). The findings highlight the effectiveness of this training model in enhancing clinical educators' learning outcomes. The study suggests that incorporating experiential learning into clinical education can be a valuable strategy for improving the competence of clinical educators and subsequently achieving better clinical achievements.